PENGARUH TEKANAN DAN SUHU TERHADAP KERAPATAN DAN NILAI KALOR BRIKET ARANG LIMBAH SERBUK MERANTI MERAH - J. Titarsole; J. J. Fransz (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
This study aims to determine the effect of pressure and temperature on the density and calorific value of red meranti sawdust charcoal briquettes (Sorea. selanica). This study used a factorial complete randomized design with 3 replications. Factors used are A factor (pressure 1 ton, 2 tons and 3 tons) and B factor (temperature 100ºC, 200ºC and 300ºC). The results showed that the highest density based on the pressure factor (A) was 3 tons (a3) of 0.478 gm/cm3 and the lowest was in the 1 ton (a1) treatment of 0.377 gm/cm3, while based on temperature (B) the highest was in the 300ºC temperature treatment ( b3) of 0.479 gr/cm3 and the lowest at 100ºC (b1) of 0.378 gr/cm3. The highest calorific value based on the pressure factor (A) is 2 tons (a2) of 3734.3991 cal/gram and the lowest is in the 1 ton (a1) treatment of 3731.6027 cal/gram, while based on the temperature treatment (B) the highest is at a temperature 200ºC (b2) of 3835.3992 cal/gram and the lowest at 100ºC (b1) of 3732.6028 cal/gram, lower than the Indonesian National Standard. The pressure factor (A) have an effect on the density and calorific value while the temperature factor (B) and the interaction AB has no effect.